Aerobic and resistance exercise-regulated phosphoproteome and acetylproteome modifications in human skeletal muscle - Mark W. Pataky; Carrie J. Heppelmann; Kyle J. Sevits; Aneesh K. Asokan; Arathi Prabha Kumar; Katherine A. Klaus; Surendra Dasari; Hawley E. Kunz; Matthew D. Strub; Matthew M. Robinson; Joshua J. Coon; Ian R. Lanza; et al. (Nature Communications)
Abstract Despite indisputable benefits of different exercise modes, the molecular underpinnings of their divergent responses remain unclear. We investigate post-translational modifications in human skeletal muscle following 12 weeks of high-intensity aerobic interval or resistance exercise training. High-intensity aerobic training induces acetylproteome modifications including several mitochondrial proteins, indicating post-translational regulation of energetics machinery, whereas resistance exercise training regulates phosphoproteomic modifications of contractile/cytoskeletal machinery, consistent with greater strength. Furthermore, despite similar transcriptional responses to a single acute bout of aerobic and resistance exercise, more robust phosphoproteomic and metabolomic responses occur with acute aerobic exercise, including phosphorylation of structural/contractile and membrane transport machinery, and the nascent polypeptide-associated complex-α, a regulator of protein translation. Together, our findings provide new insight on the intricate phosphoproteomic and acetylproteomic modifications in muscle that potentially explain physiological responses to different modes of chronic and acute exercise. This study is registered with ClinicalTrials.gov, numbers NCT01477164 and NCT04158375.